VprBP mitigates TGF-β and Activin signaling by promoting Smurf1-mediated type I receptor degradation. (10th July 2019) - Li, Yihao; Cui, Chao; Xie, Feng; Kiełbasa, Szymon; Mei, Hailiang; van Dinther, Maarten; van Dam, Hans; Bauer, Andreas; Zhang, Long; ten Dijke, Peter
Abstract: The transforming growth factor-β (TGF-β ) family controls embryogenesis, stem cell differentiation, and tissue homeostasis. However, how post-translation modifications contribute to fine-tuning of TGF-β family signaling responses is not well understood. Inhibitory (I)-Smads can antagonize TGF-β /Smad signaling by recruiting Smurf E3 ubiquitin ligases to target the active TGF-β receptor for proteasomal degradation. A proteomic interaction screen identified Vpr binding protein (VprBP) as novel binding partner of Smad7. Mis-expression studies revealed that VprBP negatively controls Smad2 phosphorylation, Smad2–Smad4 interaction, as well as TGF-β target gene expression. VprBP was found to promote Smad7–Smurf1–Tβ RI complex formation and induce proteasomal degradation of TGF-β type I receptor (Tβ RI). Moreover, VprBP appears to stabilize Smurf1 by suppressing Smurf1 poly-ubiquitination. In multiple adult and mouse embryonic stem cells, depletion of VprBP promotes TGF-β or Activin-induced responses. In the mouse embryo VprBP expression negatively correlates with mesoderm marker expression, and VprBP attenuated mesoderm induction during zebrafish embryogenesis. Our findings thereby uncover a novel regulatory mechanism by which Smurf1 controls the TGF-β and Activin cascade and identify VprBP as a critical determinant of embryonic mesoderm induction.